2009
DOI: 10.1093/toxsci/kfp053
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Chlorpyrifos and Methyl Parathion Exposure Alters Radial-Arm Maze Performance in Juvenile and Adult Rats

Abstract: Although the use of organophosphate (OP) insecticides has been restricted, sufficient exposure can occur to induce detrimental neurobehavioral effects. In this study, we measured physical and reflex development and spatial learning and memory in rats repeatedly exposed to incremental doses of chlorpyrifos (CPS) and methyl parathion (MPS) from postnatal day (PND) 1 to PND21. Other than decreased body weight in the higher dosage groups, no effects on physical or reflex development were observed. Significant hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
56
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 71 publications
7
56
0
1
Order By: Relevance
“…Considering that the cholinergic system plays an important role in brain development, 36,37 and subclinically lower AChE activity has been associated with measureable physiologic changes in children, 38 our findings support the hypothesis that AChE inhibition is an important mechanism of neurotoxicity of cholinesterase inhibitor pesticides. Chlorpyrifos has been reported to inhibit brain AChE activity in rats, [16][17][18][19] with significant AChE inhibition in the hippocampus, 20 a structure with important roles in memory, spatial navigation, imagination, and perhaps inhibitory control. [39][40][41] However, AChE inhibition is an indicator of exposure, and other neurotoxic mechanisms may also be present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the cholinergic system plays an important role in brain development, 36,37 and subclinically lower AChE activity has been associated with measureable physiologic changes in children, 38 our findings support the hypothesis that AChE inhibition is an important mechanism of neurotoxicity of cholinesterase inhibitor pesticides. Chlorpyrifos has been reported to inhibit brain AChE activity in rats, [16][17][18][19] with significant AChE inhibition in the hippocampus, 20 a structure with important roles in memory, spatial navigation, imagination, and perhaps inhibitory control. [39][40][41] However, AChE inhibition is an indicator of exposure, and other neurotoxic mechanisms may also be present.…”
Section: Discussionmentioning
confidence: 99%
“…Next, erythrocytic AChE is similar to neuronal AChE activity, 2 and brain AChE has been reported to be diminished after chlorpyrifos exposure in rats. [16][17][18][19][20] In addition, erythrocytic AChE has a long recovery time (82 days), 21 low intraindividual variability, 22 and is considered to be a stable assessment of past exposures to cholinesterase inhibitors, 23 although it is less sensitive and specific than most pesticide quantification methods. 23,24 Finally, we previously found that a single measure of AChE activity can be an adequate indicator of pesticide exposure in epidemiologic studies of children.…”
mentioning
confidence: 99%
“…Prenatally organophosphate exposed children had greater decreases in attention among boys versus girls in agricultural areas in California [30] and in working memory among children in New York City [31]. Animal studies have also determined greater detrimental neurochemical and behavioral effects among males after exposure to organophosphates [32].…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic and erythrocytic AChE are functionally similar so changes in erythrocytic AChE activity may reflect the situation in target tissues, especially in the brain. OPs has been reported to inhibit brain AChE activity in rats with significant AChE inhibition in the hippocampus [32]. Hippocampus is a structure with important roles in depression, suicidal events, memory and imagination [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation